Phage‐Host Interactions in Flavobacterium Pathogens and the Potential of Phage‐Based Disease Control in Salmonid Aquaculture - Lotta A. I. Landor; Valeria Ruffo; Lotta‐Riina Sundberg; Lone Madsen; Mathias Middelboe (Reviews in Aquaculture, 2026)
A major bottleneck to the projected expansion of the aquaculture industry is disease outbreaks caused by bacterial pathogens. Fish diseases caused by Flavobacterium pathogens are persistent in salmonid aquaculture, and treatment is limited to antimicrobials, which contaminate the aquatic environment and promote antimicrobial resistance. Bacteriophages (phages) are viruses that naturally kill bacteria, and Flavobacterium ‐infecting phages have shown promise in preventing and controlling disease and biofilm formation in aquaculture. This review compiles current knowledge on Flavobacterium ‐phage interactions and applications. We outline the diversity and distribution of Flavobacterium hosts and phages, and discuss the connection between the type IX secretion system, the gliding motility machinery, phage susceptibility, and host virulence. While there is still much to learn about phage resistance mechanisms, the frequent observation that phage resistance is associated with loss of pathogen virulence points to phages as a promising avenue for future pathogen control. Phages infecting Flavobacterium hosts also show persistence to environmental and storage conditions, making them potentially suitable for the development of phage products. Finally, we assess the remaining challenges concerning regulation of phage products, manufacturing at scale, as well as unresolved research questions that need to be addressed to supply the aquaculture industry with alternative treatment and prevention methods in the future.